Global Well-posedness of Classical Solutions with Large Initial Data to the Two-dimensional Isentropic Compressible Navier-Stokes Equations (Journal of Partial Differential Equations, 2014)
We establish the global existence and uniqueness of classical solutions to the Cauchy problem for the two-dimensional isentropic compressible Navier-Stokes equations with smooth initial data under the assumption that the viscosity coefficient μ is large enough. Here we do not require that the initial data is small.
Keywords: Isentropic compressible Navier-Stokes equations; large viscosity coefficient; global classical solutions